2020
DOI: 10.1111/odi.13369
|View full text |Cite
|
Sign up to set email alerts
|

Syndromes with gingival fibromatosis: A systematic review

Abstract: Objective The aim of systematic review was to describe the phenotypes and molecular profiles of syndromes with gingival fibromatosis (GF). Methods A comprehensive search of PubMed, LILACS, Livivo, Scopus, and Web of Science was conducted using key terms relevant to the research questions and supplemented by a gray literature search. The Methodological Quality and Synthesis of Case Series and Case Reports in association with the Case Series and Prevalence Studies from the Joanna Briggs Institute critical apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…Consistent with the ERS gingival phenotype, characterized by ECM accumulation and calcium deposition, most of the dysregulated proteins have biomineralization functions (49) and were previously associated to ectopic calcification and/or fibrosis (21,(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 70%
“…Consistent with the ERS gingival phenotype, characterized by ECM accumulation and calcium deposition, most of the dysregulated proteins have biomineralization functions (49) and were previously associated to ectopic calcification and/or fibrosis (21,(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 70%
“…In addition, there is a consensus that GF must be surgically removed conservatively, with excision of the enlarged gingival tissues and preservation of the tooth. 8 Although different techniques are possibly employed (scalpels, electrosurgery, and lasers), HPLs seem to be equally efficient or superior to scalpels. 7 Many studies reported the use of HPL in oral soft tissues, with good results, and this is the first report of this technique in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence is unknown, the incidence is 1:175,000 according to phenotype and 1:350,000 according to genotype, and equal between males and females. HGF is commonly described as an isolated disorder (non-syndromic), or it can develop as a part of a syndrome (syndromic) like Cowden's syndrome, Zimmermann-laband syndrome, Cross syndrome, Rutherford syndrome, Ramon syndrome, Jones syndrome, Costello syndrome, Ectro-amelia syndrome, and hyaline fibromatosis syndrome [15]. In this part, we mainly discuss non-syndromic HGF.…”
Section: Hereditary Gingival Fibromatosismentioning
confidence: 99%
“…In severe cases, the teeth are almost completely covered. The firm yet painless enlargement of the gingiva does not commonly affect the alveolar bone but can lead to the development of pseudo-pockets, which facilitate plaque accumulation due to suboptimal daily oral hygiene [13][14][15][16].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation